2019
DOI: 10.1177/2050312119874622
|View full text |Cite|
|
Sign up to set email alerts
|

Factors associated with cerebral edema in children under 5 years of age admitted in an intensive care unit and their outcome

Abstract: Objective: We aimed to evaluate risk factors and outcome of cerebral edema in children with diarrhea. Methods: In this retrospective chart analysis, data of all diarrheal children under 5 years of age having convulsion and admitted in intensive care unit were retrieved from an electronic medical record system of Dhaka Hospital of International Centre for Diarrhoeal Disease Research, Bangladesh, from 1st January 2011 to 31st December 2016. Comparison of clinical and laboratory characteristics was made between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…10,11 In contrast, studies examining the rate of sodium correction in infants and older children have not demonstrated adverse outcomes with rapid correction. [15][16][17][18] An explanation as to why neonates may be more vulnerable to seizures related to rapid hypernatremia correction despite the greater intracranial compliance of .8 this age group 19 remains unknown. We excluded infants younger than age 6 months in our study due to the unique fluid and electrolyte requirements and insensible losses in this age group; however, our outcomes were consistent across subgroup analyses for children aged 6-18 months compared with older children.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 In contrast, studies examining the rate of sodium correction in infants and older children have not demonstrated adverse outcomes with rapid correction. [15][16][17][18] An explanation as to why neonates may be more vulnerable to seizures related to rapid hypernatremia correction despite the greater intracranial compliance of .8 this age group 19 remains unknown. We excluded infants younger than age 6 months in our study due to the unique fluid and electrolyte requirements and insensible losses in this age group; however, our outcomes were consistent across subgroup analyses for children aged 6-18 months compared with older children.…”
Section: Discussionmentioning
confidence: 99%
“…The highest odds of death were seen in patients with cardiac arrest and cerebral edema, two entities associated with increased mortality in other injured patients. 8,9 Invasive procedures including mechanical ventilation and central venous line insertion were also associated with increased odds of death. Of the minority of patients who received ECMO, there was no association with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral edema is a potentially non-specific and fatal complication of DKA, which may occur focally or diffusely after any neurological damage. This condition has many manifestations and is associated with numerous cellular physiological changes (40,41) and usually presents with changes in the level of consciousness, bradycardia, hypertension (42,43), respiratory pattern abnormalities, and plantar extensor response on the lesion site (44). According to the results of a similar review study aimed at evaluating cerebral edema in diabetic children, the pathophysiology of cerebral edema was divided into three categories: cytotoxic, vasogenic, and osmotic and the role of specific aspects of DKA treatment in the development of CE continues to be controversial (41).…”
Section: Introductionmentioning
confidence: 99%